Cervical Intramedullary Cavernous Haemangioma: A Rare Cause of Acute Hemiparesis - Moses, Caisha Nivenia; Wan Mohamad, Wan Syahmi; Kamarul Aryffin Baharuddin,; Chan, Shu Bing (IIUM Medical Journal Malaysia, 2025)
This case report describes a 45-year-old female who presented with acute hemiparesis and was initially diagnosed with acute ischemic stroke. Subsequent evaluation of her non-contrast computed tomography (NCCT) brain revealed a lesion in her spinal cord, which was further identified as intramedullary mass on cervical spine magnetic resonance imaging (MRI). This case underscores the importance of differential diagnosis in patients presented with acute hemiparesis, comprehensive assessment of NCCT scan, and the crucial role of MRI in diagnosing spinal cord lesions. Surgical intervention, involving laminectomy and excision of the lesion, was essential and resulted in significant postoperative improvement, highlighting the pivotal role of surgery in managing such conditions.